TINJAUAN HISTORIS TERHADAP KEPPRES NO. 24 TAHUN 2016 TENTANG HARI LAHIR PANCASILA - I Gusti Ngurah Santika (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
This research aims to conduct a historical review of the Presidential Decree No. 24 of 2016 concerning the Birth of Pancasila. The method used in this research is literature or liberary research. The results of this research indicated that the determination of June 1st as the Birth of Pancasila has been championed by Megawati Soekarno Putri, PDI-P, and Taufiq Kiemas since the administration of President Susilo Bambang Yudhoyono. The commemoration of June 1st as the Birth of Pancasila was finally successfully fought for during President Jokowi's administration. Presidential Decree No. 24 of 2016 is based on the consideration that Ir. Soekarno was the first to make a speech proposing Pancasila as the basis of the state in the BPUPKI Session. Meanwhile, President Jokowi's reasons and motivation for establishing June 1st as the Birth of Pancasila are so that the public will know the origins of Pancasila, respect the struggle of the nation's founders in exploring, formulating and establishing Pancasila, stopping the polemic of who was the digger and founder of Pancasila, and preserving and preserving Pancasila through practice.